2012
DOI: 10.1038/cdd.2012.63
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lipid stores and metabolism by lipophagy

Abstract: Intracellular lipids are stored in lipid droplets (LDs) and metabolized by cytoplasmic neutral hydrolases to supply lipids for cell use. Recently, an alternative pathway of lipid metabolism through the lysosomal degradative pathway of autophagy has been described and termed lipophagy. In this form of lipid metabolism, LD triglycerides (TGs) and cholesterol are taken up by autophagosomes and delivered to lysosomes for degradation by acidic hydrolases. Free fatty acids generated by lipophagy from the breakdown o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
335
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(354 citation statements)
references
References 95 publications
11
335
0
Order By: Relevance
“…Evidence is also available indicating that excessive steatosis and fibrosis dramatically inhibited hepatic function in various pathological conditions including aging (Kuk et al., 2009). More importantly, autophagy has been reported to be linked to lipid metabolism (Liu & Czaja, 2013; Liu, Guo, et al., 2016; Singh et al., 2009; Yang, Li, Fu, Calay, & Hotamisligil, 2010). Intracellular lipids regulate levels of autophagy, and inhibition of autophagy increases hepatic lipid storage in cultured hepatocytes and mouse liver during starvation (Liu & Czaja, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence is also available indicating that excessive steatosis and fibrosis dramatically inhibited hepatic function in various pathological conditions including aging (Kuk et al., 2009). More importantly, autophagy has been reported to be linked to lipid metabolism (Liu & Czaja, 2013; Liu, Guo, et al., 2016; Singh et al., 2009; Yang, Li, Fu, Calay, & Hotamisligil, 2010). Intracellular lipids regulate levels of autophagy, and inhibition of autophagy increases hepatic lipid storage in cultured hepatocytes and mouse liver during starvation (Liu & Czaja, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, autophagy has been reported to be linked to lipid metabolism (Liu & Czaja, 2013; Liu, Guo, et al., 2016; Singh et al., 2009; Yang, Li, Fu, Calay, & Hotamisligil, 2010). Intracellular lipids regulate levels of autophagy, and inhibition of autophagy increases hepatic lipid storage in cultured hepatocytes and mouse liver during starvation (Liu & Czaja, 2013). In our study, the overt steatosis and fibrosis in aged livers were markedly attenuated by young plasma injections, suggesting that young blood may preserve the liver from fibrosis in aging.…”
Section: Discussionmentioning
confidence: 99%
“…Although LC3 may be directly recruited to lipid droplets to initiate the formation of a limiting membrane, this idea is controversial 76 . SNARE (SNAP receptor) proteins that have been implicated in both autophagosome biogenesis and lipid droplet fusion may also facilitate macrolipophagy 77 . The identity of the receptors targeting lipids to autophagosomes remains unclear, but recent research has indicated that dynamin 2, a GTPase involved in membrane scission, favours the degradation of hepatic lipid droplets by promoting the maturation of the autophagic compartment 78 .…”
Section: Hepatic Steatosismentioning
confidence: 99%
“…LC3 can be recruited to LD, suggesting that LD may be selectively removed by autophagy (a process termed lipophagy) (162). The mechanisms of LD sequestration into autophagosomes remain unclear, but they may involve the soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs) and LC3, which can associate with LDs in the absence of an autophagosomal membrane (100). Defects in lipophagy may result in altered mitochondrial b-oxidation, along with a failure to supply lipids for structural elements of the cell or to regulate lipid-dependent cell signaling (100).…”
Section: Lipophagy and Pexophagymentioning
confidence: 99%